Anthropometry and fitness of young elite soccer players by field position - Portes, L. A.; Canhadas, I. L.; Silva, R. L. P.; Cristina de Oliveira, N. (Sport Sciences for Health, 2015)
Purpose: The present study aimed at determining anthropometric and physical fitness characteristics of boys, who were previously selected to participate in specialized soccer training, according to their positions in the game field. Methods: Two hundred and ninety-six boys ageing from 10 to 13 years old were evaluated, after being recruited and assigned to the position each one would play, as determined by the coaches: goalkeepers (n = 26), defenders (n = 77), midfielders (n = 113) and forwards (n = 80). All of them had been through selection phase in a soccer club and started specialized training 3 times/week, 3 h/day, 2 months before the assessment. Results: Goalkeepers and defenders are taller, heavier and have more lean mass than players from other positions (p < .01). They also have more flexibility, lower limb strength and muscle power than midfielders and forwards (p < .05). Forwards, in turn, present less adiposity than midfielders, defenders and goalkeepers (12.1 ± 4.5 vs. 14.0 ± 5.7; 15.3 ± 5.1 and 17.0 ± 6.7, respectively, p < .01). Agility, elbow flexion strength and maximal oxygen consumption did not differ significantly among players of different field positions. Conclusion: Data show clear differences among athletes from each field position. Goalkeepers and defenders are the tallest and heaviest of all players, and they also have more lean mass than midfielders and forwards. Flexibility, lower limb strength and muscle power are highlighted features in goalkeepers when compared to players from other field positions. Conversely, forwards present lower adiposity than athletes from all other positions. ABSTRACT FROM AUTHOR